Sociology of agriculture: technology,labour,development and social classes in an international perspective - Bonanno, Alessandro (New Delhi, 1989)
The book contains examples of the recent work of members of the Sociology of Agriculture' Research Committee, a group affiliated to the International Sociological Association. It is divided into three parts which address ongoing concerns and issues related to the development and change of agriculture and food production at the international and domestic levels. In the first part of the volume the relationship between the development and implementation of technology in agriculture is explored with respect to both new technologies, such as bio-technology, and conventional technologies. The second part discusses the impact of changes in society and agriculture on the labour market, labour structure and the relations of production in rural areas. The third and final portion investigates patterns of rural development as they relate to agriculture, its structure and its people. In the Introduction, the editor provides an outline of the scientific status of Sociology of Agriculture and the manners in which it differs from the parent discipline of Rural Sociology.
Keywords: Rural development